Grafik Ve Fotoğraf Alanı Baskıya Hazırlık Modüllerine Yönelik Bir Yeterlilik Araştırması - Coşkun, Cumhur (The Turkish Online Journal of Design Art and Communication, 2015)
The very basic aim of this investigation is to determine the effectiveness of prepress (make-ready) module of the printing preparation course which is an applied course of Graphics and Photograph Department in Vocational and Technical High Schools and constituting an example module suitable for the educational material which is concluded as an enriched design for being part of prepress (make-ready) module in accordance with these detected results. In accordance with this chief objective, a 5-point Likert type scale was formed and utilized for gathering data in conformity with subobjectives. The study group of this investigation is formed by 30 teachers who give lessons in printing preparation and working in Graphic and Photograph Departments of Vocational and Technical High Schools were selected by means of purposeful sampling. In order to verify the content validity of the scale, the supervision of experts is benefited from. In the analysis of reliability, interior consistency Cronbach Alpha coefficient was used. In order to analyze the data SPSS software was used and the data of the arithmetic mean, frequency, percentage and standard deviation values calculated were tabulated and interpreted according to the findings obtained. As a result of findings obtained; it is concluded that the module of prepress (make-ready) has problem of to supporting individual learning, content and up-to-dateness which are the reasons for it being revised again.
Keywords: Ders Programları; Eğitim; Grafik Eğitimi; Baskıya Hazırlık; Curriculum; Education; Graphics Education; Printing Prepation